2004
DOI: 10.1590/s0036-46652004000500007
|View full text |Cite
|
Sign up to set email alerts
|

Sanitary conditions of a colony of urban feral cats (Felis catus Linnaeus, 1758) in a zoological garden of Rio de Janeiro, Brazil

Abstract: The colony of urban stray cats living in the Rio de Janeiro zoological garden was studied in order to develop a population and health control program. As many cats as possible were captured during two months (47 animals) and were classified according to gender, age, weight and coat markings. They were submitted to a general health evaluation, examined for the presence of ectoparasites and sent to a surgical neutering program. All animals had a blood sample drawn for CBC, platelet count, heartworm and retroviru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
2
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
0
11
2
5
Order By: Relevance
“…Hosie et al (1989), showed that infection frequently occurs after the first year of age and its prevalence is higher in elderly cats. Serological studies showed the presence of anti-FIV antibodies in Sao Paulo (20.5%) (Reche et al, 1997) and Rio de Janeiro (16.7 and 21.0%) state (Souza et al, 2002;Reche et al, 1997;Mendes-de-Almeida et al, 2004). The higher number of anti-FIV cats in Sao Paulo and Rio de Janeiro comparing to Belo Horizonte, it's probably because serological methods are less specific and can generate false positive results (Hosie and Jarrett, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…Hosie et al (1989), showed that infection frequently occurs after the first year of age and its prevalence is higher in elderly cats. Serological studies showed the presence of anti-FIV antibodies in Sao Paulo (20.5%) (Reche et al, 1997) and Rio de Janeiro (16.7 and 21.0%) state (Souza et al, 2002;Reche et al, 1997;Mendes-de-Almeida et al, 2004). The higher number of anti-FIV cats in Sao Paulo and Rio de Janeiro comparing to Belo Horizonte, it's probably because serological methods are less specific and can generate false positive results (Hosie and Jarrett, 1990).…”
Section: Resultsmentioning
confidence: 99%
“…inferiores às observadas no presente estudo foram detectadas através da PCR no Rio de Janeiro (12,1%) ), em São Luís (14,5%) (Braga et al 2012) e em Jaboticabal (6,5%) (Bartoli et al 2012). Entretanto, há relatos de taxas de infecção por hemoplasmas superiores ao observado no presente estudo e que foram detectadas através do esfregaço sanguíneo, como os 38% reportado por Mendes-de--Almeida (2004) de hemoplasmas através do esfregaço sanguíneo, técnicas como a PCR e o sequenciamento devem ser empregados para evitar resultados falso-positivos e falso-negativos (Sykes 2010). A análise comparativa da ocorrência dos hemoparasitos estudados demonstrou que não houve diferença entre a ocorrência de 'Candidatus M. haemominutum' e 'Candidatus M. turicensis ' (p=0,1030), contudo, esses agentes tiveram ocorrência superior a M. haemofelis (p=0,0022 e p=0,0001, respectivamente).…”
Section: Discussionunclassified
“…[4][5][6][7][8] The purpose of this study was to assess the biochemistry variables from a large group of free-roaming cats who presented to a spay/neuter program in New York, NY, USA, determine age-and gender-specific reference intervals when appropriate, and identify any trends within this population that may be of clinical importance.…”
Section: Introductionmentioning
confidence: 99%